Magnetic blocking in a linear iron(I) complex - Zadrozny, Joseph M.; Xiao, Dianne J.; Atanasov, Mihail; Long, Gary J.; Grandjean, Fernande; Neese, Frank; Long, Jeffrey R. (Nature chemistry, 2013)
Single-molecule magnets that contain one spin centre may represent the smallest possible unit for spin-based computational devices. Such applications, however, require the realization of molecules with a substantial energy barrier for spin inversion, achieved through a large axial magnetic anisotropy. Recently, significant progress has been made in this regard by using lanthanide centres such as terbium( III ) and dysprosium( III ), whose anisotropy can lead to extremely high relaxation barriers. We contend that similar effects should be achievable with transition metals by maintaining a low coordination number to restrict the magnitude of the d -orbital ligand-field splitting energy (which tends to hinder the development of large anisotropies). Herein we report the first two-coordinate complex of iron( I ), [Fe(C(SiMe 3 ) 3 ) 2 ] − , for which alternating current magnetic susceptibility measurements reveal slow magnetic relaxation below 29 K in a zero applied direct-current field. This S = complex exhibits an effective spin-reversal barrier of U eff = 226(4) cm −1 , the largest yet observed for a single-molecule magnet based on a transition metal, and displays magnetic blocking below 4.5 K. Mononuclear complexes of certain lanthanide ions are known to have large magnetization reversal barriers caused by strong spin–orbit coupling. Now, careful tuning of the ligand field of a transition metal complex has engendered a comparable spin-reversal barrier — and in turn magnetic blocking at 4.5 K.